THE IMPACT OF ENHANCING THE SOCIO-ECONOMIC DEVELOPMENT OF TOURISM ON THE LOCAL COMMUNITY OF JERASH - Ahmad Mohammad Alzouby, Imad Akram Al-Hashimi, Anwar Fareed Alramadneh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In recent there are a number of socio-economic development selections in Jerash, but its impact is largely intangible for local community. For tourism to the local community of Jerash, perhaps the most important thing that distinguishes the research is that most of the previous research of Jerash studies the attitudes and perceptions of the local population, but this research used quantitative and qualitative methods in the research methodology where he measured the impact of promoting socio-economic development through regular interviews, observation and the work of a linear regression model that measures the impact of the independent variable (number of employees in the tourism sector, the number of tourists, the rate of expenditure) on the variable income adopted for the first model and the model was distributed the income/retail price index for the second model as well as measuring the attitudes and perceptions of the community through questionnaires distributed to local community and stakeholders. The results were analyzed through the statistical program SPSS as well as worked SWOT analysis of current manifestations to enhancing socio-economic development. In addition to the local community with tourists through the manifestations of development in Jerash, however, there are many aspects of development that have negatively affected the local community, perhaps the most important of which is the failure to integrate the community with tourists and thus led to a decrease in the material return of the local community due to the lack of government plans and strategies. It is suggested that more community awareness and education programmers be researched in order to obtain positive benefits and reduce the negative effects of tourism.